2022
DOI: 10.1177/02645505221087976
|View full text |Cite
|
Sign up to set email alerts
|

French and scottish probation during the first lockdown. In search of the heart and soul of probation

Abstract: In March 2020 in response to the global pandemic, countries across Europe ordered businesses and offices to close and their citizens to stay at home. This paper is part of a wider investigation, which explores what happened to probation services in France and in Scotland during this time of national emergency. Qualitative interviews with 29 French and 27 Scottish probation staff took place during the initial lockdown, the authors wishing to capture the personal and organisational experience of practising proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…As immediate issues (health, safety, IT equipment and so on) were addressed, and service became more stable, managers then turned to continuity of service. They had to decide what constituted essential probation (Herzog-Evans and Sturgeon, 2022b), which needed to be salvaged. Part of the answer resided in determining where the priorities lay (Viglione et al, 2020), notably regarding risk levels and offenders’ needs.The amount of lists that we have is endless: from MAPPA lists to Caledonian [domestic abuse] lists, to high-risk lists… (M8)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As immediate issues (health, safety, IT equipment and so on) were addressed, and service became more stable, managers then turned to continuity of service. They had to decide what constituted essential probation (Herzog-Evans and Sturgeon, 2022b), which needed to be salvaged. Part of the answer resided in determining where the priorities lay (Viglione et al, 2020), notably regarding risk levels and offenders’ needs.The amount of lists that we have is endless: from MAPPA lists to Caledonian [domestic abuse] lists, to high-risk lists… (M8)…”
Section: Resultsmentioning
confidence: 99%
“…The Covid-19 lockdown ripped up patterns of working that had been established for over a hundred years (Herzog-Evans and Sturgeon, 2022b; Martin and Zettler, 2022) and the lockdown of individuals and families in their homes meant that staff, including managers, had to be allowed to improvise. Indeed, a key TL competence attribute is flexibility and the need for flexibility appeared to be particularly salient during the lockdown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of studies conducted by Herzog-Evans and Sturgeon, 2022a, 2022b, 2022c interviewed PPs during the early stages of the COVID-19 lockdown. The first study explored how managers responded to PPs within Scotland.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the best managers during a time of crisis such as this were the servant leaders who prioritise the fundamental human needs of their staff and reduce their level of uncertainty (Herzog-Evans and Sturgeon, 2022a). The other two studies (Herzog-Evans and Sturgeon, 2022b, 2022c) explored their personal and organisational experiences in a sample from Scotland and France. They found that in both jurisdictions, the majority of partner agencies were closed which meant that they could not provide the appropriate medical, mental health, or substance-use treatment for PoP as they normally would (Herzog-Evans and Sturgeon, 2022b).…”
Section: Introductionmentioning
confidence: 99%